The Impact of Pesticide Wastewater on Environmental Health: A Bibliometric Analysis - Putri, Dhea Kasnelia; Yuniarti, Elsa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Pesticide wastewater is water containing dissolved or dispersed pesticide residues that can threaten environmental health. This study aims to assess the impact of pesticide wastewater on environmental health. The method employed was a literature review of the Scopus database using the keywords “pesticide AND wastewater AND health.” Data were analyzed with VOSviewer to map the interrelationships among keywords. The results revealed three maps with four color clusters highlighting the keywords “pesticide,” “wastewater,” and “health.” In conclusion, bibliometric analysis is effective for identifying research themes and guiding future studies. The implications of these findings are that bibliometric analysis can enhance understanding of research trends on pesticide wastewater and foster the development of more in‑depth studies and more effective pesticide wastewater management strategies.